Humanisasi-Inklusifisasi Pendidikan Islam Dalam Konteks Multikulturalisme - sholahuddin - (Millah: Journal of Religious Studies, 2005)
After the fall of Soeharto regime, educational academic discourses colored by the humanization and pluralistic ^stem. The pluralistic and humanization educational ^stem are necessary to enhance the democratic state and empower civil society from state intervention. In this case, Islamic educational system should be grow and changed from the normative and emphasize on the transferring knowledge from teacher to student to more than that. The participation of student in terms of Islamic educational system is the new construction of that. With student's participation the relationship between teacher and student become more egaliter and equal This paper tries to criticize Islamic educational system within the Islamic institution like, Madrasah, Pesantren and many others. Actually the writer will emphasis^ how to apply humanistic values in the sense of Islamic educational system, such us, inclusivism, tolerance, trust and many others. Finally, the writer emphasizes the important of inter-religious education in term of Islamic education.